2017
DOI: 10.1089/mdr.2016.0186
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Fluoroquinolone-ResistantHaemophilus parainfluenzaeClinical Isolates in Spain

Abstract: Multiple H. parainfluenzae fluoroquinolone-resistant isolates grouped in the same area in a short period of time showed diverse substitutions in QRDR of gyrA/parC and were not clonally related, indicating individual emergence. In addition, we described the first report of Glu88Lys substitution in ParC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…Interestingly, for the isolates with a Ͼ4-fold increase in fluoroquinolone MIC values from both arms, 3 out of the 4 isolates were genetically unrelated. Previous studies from Spain and South Africa reported fluoroquinolone resistance arising from mutations in the QRDR as well as plasmid-mediated resistance (9,10). The mutations observed in H. parainfluenzae in this study were also observed in isolates reported in the Spanish and South African studies.…”
Section: Discussionsupporting
confidence: 75%
“…Interestingly, for the isolates with a Ͼ4-fold increase in fluoroquinolone MIC values from both arms, 3 out of the 4 isolates were genetically unrelated. Previous studies from Spain and South Africa reported fluoroquinolone resistance arising from mutations in the QRDR as well as plasmid-mediated resistance (9,10). The mutations observed in H. parainfluenzae in this study were also observed in isolates reported in the Spanish and South African studies.…”
Section: Discussionsupporting
confidence: 75%